Anatomical Studies of the Gastrointestinal Tract of snake Malpolon monspessulanus insignitus (Geoffroy, 1809) - Mohammed, Ezaldin; Abd-Alhafid, Youssef; Jala, Hamed (Libyan Journal of Science &Technology, 2022)
Studies aim to study the morphometrical and anatomical features of a gastrointestinal tract of Malpolon insignitus, and compared with that of other examined reptiles So, It is clear that the tissues in the gastrointestinal tract adapt to feed the meat. The wall of the esophagus, stomach, small intestine, and large intestine is a buildup of four layers from outside inwards are serosa, muscularies, submucosa and mucosa. The esophagus was longer than the stomach and It may measure one-quarter the body length of the snake it is highly stretch to facilitate movement the food to the stomach. The mucosal epithelium was consist of simple and compound stomach glands and consist of three types of glands; they are the cardiac glands, pyloric glands, and fundus glands. The majority of the mucosal folds were primary folds as for secondary folds were rare. The small intestine is long on and that of the animal is purely carnivorous. The small intestine is composed of short transverse loops in snakes. The intestine consists of many longitudinal folds that allow the surface area to increase digestion. The mucosa of the small intestine members in the form of leaf like villi provided with shallow branched Lieberkühn crypts at their bases. It consists of three types of cells; the endocrine cells, the goblet and the absorptive. The large intestine is short and has a larger diameter and consists of colon and rectum. The mucous membrane of the colon consists of cavernous and vertical cells, while that of the rectum is, straight and is rich in lymph spaces and goblet cells.